Fotodegradação no UV-C e fotoestabilização em polímeros utilizados na indústria médico-hospitalar - Gimenez, Jessica Caroline Ferreira (2025)
The cross-contamination concerns that came to light during the SARS-CoV-2 pandemic in 2019 emerged the use of UV-C germicidal lamps. However, despite its proven efficiency against pathogens, UV-C light promotes damage in materials such as polymers. While there is extensive literature on polymer photodegradation under UV-A and UV-B, studies on UV-C remain scarce. This gap formed the basis of the present work, which aims to provide a comprehensive understanding of UV-C effects on polypropylene (PP), a commodity polymer used in syringes, and poly(ether sulfone) (PESU), a high-performance polymer used in medical structural equipment, as well as to evaluate strategies for their photostabilization. Our findings reveal that PP became unstable during rheological measurements, displaying an unusual increase in the complex viscosity. 1H Time Domain NMR indicated that UV-C favors branching reactions over crosslinking. A Design of Experiment was employed to determine optimal PP photostabilization when combining titanium dioxide (TiO2) with few-layer graphene (FLG) or Irganox B215 (B215). Electron Paramagnetic Resonance showed that incorporating radical scavengers with TiO2 reduced hydroxyl formation by ~30% for the FLG mixture and ~25% for the B215 mixture. The study also compared continuous and cyclic UV-C exposure modes in PESU. Tensile tests demonstrated that even 1 hour of UV-C exposure significantly reduced PESU’s mechanical performance. Infrared, XPS, and rheological analysis revealed more pronounced changes in samples under cyclic exposure. Finally, PESU/FLG and PESU/graphene oxide (GO) were exposed under UV-C irradiation. Infrared results showed that FLG mitigated hydroxyl formation, while GO composites had a minimal effect. Tensile tests revealed that UV-C considerably increased the Young’s Modulus. This work provides remarkable findings into UV-C photodegradation and photostabilization of PP and PESU, highlighting subtle differences in the degradation mechanisms induced by UV-C and presenting strategies for photoprotection.